The High School Students Readiness’ to Learn English Via Online During Covid-19 Pandemic - Nurteteng Nurteteng (ELLITE, 2022)
This research aimed to identify the students’ readiness and opinion to learn English via online during the COVID-19 Pandemic. The researcher applied descriptive qualitative research method. The participants of this research are some students from SMK Muhammadiyah Aimas, MA Muhammadiyah Aimas and SMP Muhammadiyah Aimas. The researcher used random sampling as the technique for selecting the participant. The participants were taken from 10 students of each school as representatives. So, the total of the participant was 30 students who were doing the online learning. The researcher used two instruments. They were questionnaire and interview. The result of this research show that the students are not ready yet in doing online learning during this pandemic at Aimas District. It can be seen from the result of the students’ readiness questionnaire, which is 30,2 with standard deviation is 5, 640. The mean score is classified into low level of readiness. Most of them were not ready for online learning due to lack of motivation in learning, online communication, and computer/internet self-efficacy. Related with the students’ opinion, they think that online learning is not effective to apply because of the internet connection and the teaching method used.